Preparing health professions students to lead change. Issue 2 (7th May 2019) - Rotenstein, Lisa; Perez, Katherine; Wohler, Diana; Sanders, Samantha; Im, Dana; Kazberouk, Alexander; Phillips, Russell S.
Abstract : Purpose: Health care systems increasingly demand health professionals who can lead interdisciplinary teams. While physicians recognize the importance of leadership skills, few receive formal instruction in this area. This paper aims to describe how the Student Leadership Committee (SLC) at the Harvard Medical School Center for Primary Care responded to this need by creating a leadership curriculum for health professions students. Design/methodology/approach: The SLC designed an applied longitudinal leadership curriculum and taught it to medical, dentistry, nursing, public health and business students during monthly meetings over two academic years. The perceptions of the curriculum were assessed via a retrospective survey and an assessment of team functioning. Findings: Most teams met their project goals and students felt that their teams were effective. The participants reported increased confidence that they could create change in healthcare and an enhanced desire to hold leadership positions. The sessions that focused on operational skills were especially valued by the students. Practical implications: This case study presents an effective approach to delivering leadership training to health professions students, which can be replicated by other institutions. Social implications: Applied leadership training empowers health professions students to improve the health-care system and prepares them to be more effective leaders of the future health-care teams. The potential benefits of improved health-care leadership are numerous, including better patient care and improved job satisfaction among health-care workers. Originality/value: Leadership skills are often taught as abstract didactics. In contrast, the approach described here is applied to ongoing projects in an interdisciplinary setting, thereby preparing students for real-world leadership positions.